Growth, mortality and yield of Atherina boyeri Risso, 1810 from Lesina lagoon (Adriatic Sea, Italy) - Prato, Ermelinda (Array, 2020)
Population structure, growth, age, mortality and exploitation status of Atherina boyeri, caught in the period from June 2013 to May 2014 in the Lesina lagoon (Apulia region, southern Adriatic) was studied. Samples were taken each month by using beach seines . The length–weight relationship of all sand smell specimens was described by the equation W=0.012*TL 3.10; (R2= 0.84). Population parameters including the asymptotic length (L∞) and growth coefficient (K) were assessed to evaluate the stock status. The recruitment pattern was modeled with a FiSAT routine. The asymptotic length (L∞) was 111.0 mm, while the growth coefficient (K) was 0.68 year−1. The growth performance index ((φ’) reached 3.92. The total mortality coefficient “Z”, the natural mortality coefficient “M” and the fishing mortality coefficient “F” were estimated as 2.24, 1.48 and 0.76 year-1, respectively. Exploitation rate for the population of A. boyeri in the Lesina lagoon estimated as 0.34 was resulted still lower than the predicted maximum value of Emax 0.59. The probability of capture indicated that L50 was of 55.57 mm, indicating that the stock of sand smelt in Lesina lagoon is not being over-fished.